1998
DOI: 10.1073/pnas.95.3.765
|View full text |Cite
|
Sign up to set email alerts
|

Behind the scenes of functional brain imaging: A historical and physiological perspective

Abstract: At the forefront of cognitive neuroscience research in normal humans are the new techniques of functional brain imaging: positron emission tomography and magnetic resonance imaging. The signal used by positron emission tomography is based on the fact that changes in the cellular activity of the brain of normal, awake humans and laboratory animals are accompanied almost invariably by changes in local blood flow. This robust, empirical relationship has fascinated scientists for well over a hundred years. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
339
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(350 citation statements)
references
References 64 publications
9
339
0
2
Order By: Relevance
“…We have previously shown that LIVE measurements of tissue O 2 are closely related to CBF (Lowry et al, 1997), and it has been assumed, but not proven, that BOLD fMRI signals induced during neuronal activity reflect tissue O 2 levels (Dousset et al, 1999;Thompson et al, 2003Thompson et al, , 2004Thompson et al, , 2005Raichle, 1998). The findings of this study now provide strong evidence to support this assumption and demonstrate that this novel combined technology provides a means of interrogating the relationships between metabolism, haemodynamics and neuronal activity.…”
Section: Discussionsupporting
confidence: 66%
“…We have previously shown that LIVE measurements of tissue O 2 are closely related to CBF (Lowry et al, 1997), and it has been assumed, but not proven, that BOLD fMRI signals induced during neuronal activity reflect tissue O 2 levels (Dousset et al, 1999;Thompson et al, 2003Thompson et al, , 2004Thompson et al, , 2005Raichle, 1998). The findings of this study now provide strong evidence to support this assumption and demonstrate that this novel combined technology provides a means of interrogating the relationships between metabolism, haemodynamics and neuronal activity.…”
Section: Discussionsupporting
confidence: 66%
“…Nevertheless, studies in rodents using optical imaging of hemoglobin oxygenation, and physiological recordings of spiking activity and local field potentials have shown that the negative hemodynamic activity might not correspond to changes in neuronal activity (Devor, et al 2005). fMRI deactivation may also represent a direct hemodynamic response ("blood stealing") in the vascular system in response to changes in adjacent regional cerebral blood flow (rCBF), since negative BOLD signals are accompanied by decreases in rCBF (Hoge, et al 1999b;Raichle 1998;Shmuel, et al 2002;Stefanovic, et al 2004). In this model, rCBF-increases (Δ + )in activated regions would necessitate synchronous rCBF-decreases (Δ − in other brain regions (Δ + = kΔ − , where the constant k depends on the vascular distribution).…”
Section: Introductionmentioning
confidence: 99%
“…As early as the 1870s it was observed that mental activity influences regional brain physiology (Raichle 1998). Several researchers demonstrated that the surface pulsations and the temperature of the brain increase with mental activity (Raichle 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers demonstrated that the surface pulsations and the temperature of the brain increase with mental activity (Raichle 1998). The technology necessary to pursue this research was limited, and it was not until the 1950s that the first instrument for quantifying whole brain blood flow and metabolism in humans was developed (Landau et al 1956).…”
Section: Introductionmentioning
confidence: 99%